(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
This study is investigating the possibility of using pinecones as additive materials to develop a water-based drilling mud. Pinecones are environmentally friendly agricultural wastes and have no practical applications. Therefore, this study is of great importance in that it highlights the investment of these natural waste materials in practical fields. The study focused on the effectiveness of pinecone powder in a water-based drilling mud. To this end, an experimental study on five types of pinecones (Austrian pinecones, Black Hills Spruce, Sitka Spruce, Norway Spruce, and White pinecones) was performed and tested to determine their ability to reduce filter loss and also the effect of those eco-friendly materials on the rheological properties and density of the mud. In the study, 26 samples of water-based mud mixed with the different types of pinecones at different concentrations based on the weight of mud sample (1 wt%, 2 wt%, 3 wt%, 4 wt%, and 5 wt%) were used to perform the experiments. The results of the study showed that pinecones have a great ability to reduce filter loss, particularly Norway Spruce cones, which, based on this study, are considered the superior type with a concentration of 3 wt%.